Incidence and Correlates of Maternal Near Miss in Southeast Iran - Naderi, Tayebeh; Foroodnia, Shohreh; Omidi, Samaneh; Samadani, Faezeh; Nakhaee, Nouzar (International Journal of Reproductive Medicine, 2015)
This prospective study aimed to estimate the incidence and associated factors of severe maternal morbidity in southeast Iran. During a 9-month period in 2013, all women referring to eight hospitals for termination of pregnancy as well as women admitted during 42 days after the termination of pregnancy were enrolled into the study. Maternal near miss conditions were defined based on Say et al.’s recommendations. Five hundred and one cases of maternal near miss and 19,908 live births occurred in the study period, yielding a maternal near miss ratio of 25.2 per 1000 live births. This rate was 7.5 and 105 per 1000 in private and tertiary care settings, respectively. The rate of maternal death in near miss cases was 0.40% with a case:fatality ratio of 250 : 1. The most prevalent causes of near miss were severe preeclampsia (27.3%), ectopic pregnancy (18.4%), and abruptio placentae (16.2%). Higher age, higher education, and being primiparous were associated with a higher risk of near miss. Considering the high rate of maternal near miss in referral hospitals, maternal near miss surveillance system should be set up in these hospitals to identify cases of severe maternal morbidity as soon as possible.